Laterality in Emotional Language Processing in First and Second Language - Heyrani, Raheleh; Nejati, Vahid; Abbasi, Sara; Hartwigsen, Gesa (Frontiers in Psychology, 2022)
Abstract Language is a cognitive function that is asymmetrically distributed across both hemispheres, with left dominance for most linguistic operations. One key question of interest in cognitive neuroscience studies is related to the contribution of both hemispheres in bilingualism. Previous work shows a difference of both hemispheres for auditory processing of emotional and non-emotional words in bilinguals and monolinguals. In this study, we examined the differences between both hemispheres in the processing of emotional and non-emotional words of mother tongue language and foreign language. Sixty university students with Persian mother tongue and English as their second language were included. Differences between hemispheres were compared using the dichotic listening test. We tested the effect of hemisphere, language and emotion and their interaction. The right ear (associated with the left hemisphere) showed an advantage for the processing of all words in the first language, and positive words in the second language. Overall, our findings support previous studies reporting left-hemispheric dominance in late bilinguals for processing auditory stimuli.